The Role of Saponin as Feed Additive for Sustainable Poultry Production - Elizabeth Wina (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2017)
Poultry, especially broiler is an important protein source for people in developing countries. Under intensive condition, economical and efficient broiler production is disturbed by disease attack due to poor biosecurity management. Feed additives (coccidiostat and antibiotic growth promoter/AGP) that added to feed for disease prevention and growth improvement, have been banned by many countries including Indonesia. Antibiotic growth promoter can be substituted by bioactive compounds in certain plants which can improve poultry production. One of bioactive compounds is saponin which is a glycoside. This paper provides information about source and function of saponin as feed additive for poultry production. Saponin extracts or saponin containing plants have several functions, such as anticoccidia, immunostimulant, antibacteria and antifungi. Sustainable poultry production requires continues supply of feed ingredients and additive with consistent in quality. High saponin-containing plants need to be planted widely and supported by stakeholders for their avability and sustainability.